2008
DOI: 10.1007/s11999-008-0212-9
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant Organisms in Military Wounds from Iraq and Afghanistan

Abstract: Mortality from battlefield wounds has historically declined, thanks to better surgical management, faster transport of casualties, and improved antibiotics. Today, one of the major challenges facing U.S. military caregivers is the presence of multidrug-resistant organisms in orthopaedic extremity wounds. The most frequently identified resistant strains of bacteria are Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter calcoaceticus-baumannii complex. Overuse of broad-spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(142 citation statements)
references
References 54 publications
(68 reference statements)
3
138
0
1
Order By: Relevance
“…Orthopaedic infections are difficult to manage because of the formation of bacterial biofilms on implant surfaces [18], the inflammatory osteolysis that causes osseointegration failures and loosening of infected implants [27], and antibiotic resistance [9,23,29,31,33,41,45]. HDPs are promising new agents [6,14,15,19] that, owing to their unique immunomodulatory mechanisms of action, are less likely to induce bacterial resistance than are conventional antibiotics [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthopaedic infections are difficult to manage because of the formation of bacterial biofilms on implant surfaces [18], the inflammatory osteolysis that causes osseointegration failures and loosening of infected implants [27], and antibiotic resistance [9,23,29,31,33,41,45]. HDPs are promising new agents [6,14,15,19] that, owing to their unique immunomodulatory mechanisms of action, are less likely to induce bacterial resistance than are conventional antibiotics [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance and the relative lack of new therapies in development further complicate treatment of orthopaedic implant infections, which are often associated with implant loosening, loss of fracture fixation, and fracture nonunion [31,33,41]. Additionally, increased incidence of methicillin-resistant S aureus infections is a major concern in both civilian and military orthopaedics [9,29,31,45], because therapies for methicillin-resistant S aureus infections are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis led to 15.51% and 37.7% deaths in Syrian Civil War and Philippines, respectively (25). MDR bacteria were found in evacuated military personnel from Afghanistan and Iraq (26)(27)(28)(29).…”
Section: Evolution Of Antimicrobial Resistancementioning
confidence: 99%
“…[2][3][4][5] Screening performed over a period of [2003][2004][2005][2006][2007][2008][2009] revealed that an increasing number of isolates could be classified as multidrug-resistant (MDR), additionally complicating the care and treatment of infected patients. 1,6,7 Attempts have been made to prevent infection by administering antimicrobials in the field, but this has only lead to limited success. 8 Thus, there is a clear need for alternative approaches to prevent infections or treat existing infections.…”
Section: Introductionmentioning
confidence: 99%